Factors Related to Breast Self Examination (BSE) Behavior in Female Student of Public Senior High School 1 Jambi City - Hanna Audila; Rd. Halim; Marta Butar-Butar; Epid (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the proportions and the relationships between determinant factors to Breast Self Examination (BSE) behavior of Female Student in Public Senior High School 1 Jambi City. This is a cross sectional study. Collecting samples based on proportional stratified random sampling. The primary data was collected by distributing questionnaires to 63 respondents. The data analyzed by chi-square test. The result showed; there is a positive relationship between attitude, information exposure, family/mother’s support and peer’s support (poor BSE behavior is 41.3%, poor knowledge is 55.6%, negative attitude is 42.9%, never been exposed to BSE information is 39.7%, were not supported by family/mother is 46.0% and were not supported by peer is 34.9%) to BSE behavior and there is a negative relationship between knowledge (poor knowledge is 55,6%) to BSE behavior of Female Student in Public Senior High School 1 Jambi City.